Gas composition during thermochemical conversion of dry solid fuels and waste-derived slurries; Environmental Science and Pollution Research (ESPR); Vol. 30, iss. 9 - Nyashina G. S. Galina Sergeevna; Dorokhov V. V. Vadim Valerjevich; Romanov D. S. Daniil Sergeevich; Strizhak P. A. Pavel Alexandrovich (2023, 2023)
Title screen